2007
DOI: 10.1007/s00277-006-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood stem cell transplantation in multiple myeloma using oral versus I.V. melphalan

Abstract: Autologous peripheral blood stem cell transplantation is the therapy of choice for the treatment of multiple myeloma (MM) patients younger than 70 years old. Between August 1993 and November 2004, 54 patients with MM were autografted after conditioning with high-dose oral melphalan 140 mg/m(2) in combination with etoposide and carmustine (28 patients) or with high-dose melphalan 200 mg/m(2) I.V. (26 patients). The oral and IV melphalan groups were comparable. There were no significant differences in disease-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…4 However, in the past years, survival seems to be improving significantly, probably as a result of the combined use of SCT, thalidomide, new agents such as bortezomib or lenalidomide and supportive care. 1,2,4,6 We report here the long-term results of the treatment of a group of 26 patients with MM treated with a simplified autografting procedure in a single institution (Clı´nica RUIZ de Puebla, Me´xico) in a 14-year period, which indicate that the prognosis of patients with MM has improved substantially since the introduction of high-dose therapy rescued with autologous stem cell support. …”
Section: Introductionmentioning
confidence: 90%
“…4 However, in the past years, survival seems to be improving significantly, probably as a result of the combined use of SCT, thalidomide, new agents such as bortezomib or lenalidomide and supportive care. 1,2,4,6 We report here the long-term results of the treatment of a group of 26 patients with MM treated with a simplified autografting procedure in a single institution (Clı´nica RUIZ de Puebla, Me´xico) in a 14-year period, which indicate that the prognosis of patients with MM has improved substantially since the introduction of high-dose therapy rescued with autologous stem cell support. …”
Section: Introductionmentioning
confidence: 90%
“…Recent studies have shown that the dose of melphalan can be increased to 220 mg/m 2 (Garban et al , 2006), with improved PFS compared with historical controls, or to 240–300 mg/m 2 , in combination with amifostine, (Reece et al , 2006) but at the cost of increased toxicity. The addition of total body irradiation (TBI) results in increased toxicity (Moreau et al , 2002) with no improvement in response rate or PFS, whilst combination chemotherapy increases the toxicity (Capria et al , 2006; Benson et al , 2007; Vela‐Ojeda et al , 2007). Bortezomib has shown synergistic effects with melphalan without prolonged haematological toxicity.…”
Section: High Dose Therapy and Autologous Stem Cell Transplantatiomentioning
confidence: 99%
“…Despite the advantages of ASCT using melphalan at a high dose of 200 mg/m 2 over the nontransplantation approach [3], the results of ASCT in MM are still unsatisfactory because this approach is not curative, and inevitable relapse remains the primary cause of death. Few alternatives to ASCT have been explored to improve the antimyeloma activity of classic conditioning with high-dose melphalan [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%